ANALISIS PENGARUH LUAS PANEN, HARGA EKSPOR DAN PRODUKSI PANGAN NABATI TERHADAP JUMLAH EKSPOR PANGAN NABATI JAWA TENGAH TAHUN 2005-2014 - Rizki Syarif Pratama; Poniman Poniman; Endang Sulistiyani (Politeknik Negeri Semarang, 2016)
Foodstuff is one of the basic human needs and a strategic commodity to human life. The prominence of Indonesia as an agricultural country, the role of agriculture and agribusiness can be an instrument in the development of the national economy. The purpose in this research to find out the factors that affect Export Volume of Vegetable Food in Central Java. The independent variable in this study are Harvest Area, Export Prices of Vegetable Food and Production of Vegetable Food, while the dependent variable is Export Volume of Vegetable Food in Central Java. The results of this research show that the variable of Harvest Area and Export Prices of Vegerable Food has negative and significant effect toward the Export Volume of Vegetable Food in Central Java. Variable of Vegetable Food Production is a positive and significant effect toward Exports Volume of Vegetable Food in Central Java.